Chatbot-autoreply for virus topics to strengthen the profile of pancasila students with critical thinking and creativity - Abidin, Zaenal; Pradiana, Maulani (Biosfer: Jurnal Pendidikan Biologi, 2025)
The Society 5.0 era demands the younger generation to possess a Pancasila student profile. WhatsApp-based chatbot learning media can be a solution to enhance understanding of virus materials and strengthen such a profile. This research develops a chatbot autoreply-based learning media called SIMBBIOSIS (Sistem Integrasi Media Belajar Biologi Seru, Informatif, dan Sistematis ), focusing on virus materials in phase E. SIMBBIOSIS is designed to provide engaging information and interactions, as well as encourage students to think critically and creatively in solving virus-related problems. The research employs the Research and Development (R&D) method using the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The R&D process resulted in the creation of SIMBBIOSIS, a WhatsApp-based chatbot autoreply learning media. SIMBBIOSIS was designed to address the challenges of fostering critical thinking and creativity among students. During the implementation phase, the media was tested on students at MAN 3 Cirebon, with class X.9 serving as the experimental group and X.11 as the control group. The findings of this research indicate that the SIMBBIOSIS learning media effectively improved students' critical thinking and creativity. The critical thinking dimension showed significant improvement, as evidenced by an N-Gain of 82.35% and the SPSS paired T-test result of 0.0 < α (0.05). In terms of creativity, the experimental group produced more varied and innovative virus-related educational media compared to the control group, reflecting an enhancement in their ability to think creatively.